Profile of pembrolizumab in the treatment of patients with unresectable or metastatic urothelial carcinoma - Inokuchi J (Cancer Management and Research, 2019)
Junichi Inokuchi, Masatoshi EtoDepartment of Urology, Graduate School of Medical Sciences, Kyushu University, Fukuoka, JapanAbstract: The prognosis of patients with unresectable or metastatic urothelial carcinoma (UC) is poor. Platinum-based chemotherapy has been the standard first-line treatment in these patients for the past decade; however, the 5-year overall survival (OS) rate is only 13–22%. Recent advances in cancer immunology research have highlighted the pivotal role of the immune system in cancer development and progression, and new immune checkpoint inhibitors (ICIs) have demonstrated efficacy in a large variety of tumors including UC. Currently, five ICIs, including two anti-PD-1 antibodies (pembrolizumab and nivolumab) and three anti-PD-L1 antibodies (atezolizumab, avelumab, and durvalumab), have been granted approval by the US Food and Drug Administration (FDA) for patients with unresectable or metastatic UC who recurred or progressed after platinum-based chemotherapy. Among these agents, only pembrolizumab is supported by strong evidence from a large randomized Phase III trial (KEYNOTE-045). This trial demonstrated statistically significant improvements in OS for patients assigned to the pembrolizumab arm compared with the chemotherapy arm, both in the total population (HR 0.73; P=0.002) and in the population with high PD-L1 expression (HR 0.57; P=0.005). For patients with cisplatin-ineligible UC, pembrolizumab and atezolizumab were approved based on Phase II studies, with limitations on the use of these agents in patients with high tumor PD-L1 expression later imposed by the FDA. In conclusion, pembrolizumab may be a potential first-choice second-line therapy for unresectable or metastatic UC patients following platinum-based chemotherapy. Several Phase III trials are ongoing to evaluate the efficacy and toxicity of combination therapies of ICIs with chemotherapy, and ICIs with other ICIs with or without chemotherapy as first-line therapy. The results of these trials might redirect treatment strategies for patients with unresectable or metastatic UC.Keywords: urothelial carcinoma, pembrolizumab, PD-1, immune checkpoint inhibitor, PD-L1